2023
DOI: 10.3346/jkms.2023.38.e295
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride-Rich Lipoproteins and Remnant Cholesterol in Cardiovascular Disease

Ji Hye Heo,
Sang-Ho Jo

Abstract: Despite the well-established benefits of statin treatments in lowering low-density lipoprotein cholesterol (LDL-C), a significant residual risk for atherosclerotic cardiovascular disease (ASCVD) remains. Triglycerides (TGs) have long been recognized as potential residual risk factors in this context, but recent studies now disclose the substantial role of TG-rich lipoproteins (TRLs) and cholesterol components of metabolized TRLs (commonly referred to as remnant cholesterol) in atherogenesis, not just TGs alone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…While this calculation offers an approximate estimation of remnant cholesterol levels, it also includes TRL-based cholesterol that has not yet been released as remnants through lipolysis. The advantage of this method is its ability to estimate remnant cholesterol from a standard lipid profile without incurring additional costs or requiring specialized assay equipment [5 ▪ ].…”
Section: Definition Of Remnant Cholesterol and Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…While this calculation offers an approximate estimation of remnant cholesterol levels, it also includes TRL-based cholesterol that has not yet been released as remnants through lipolysis. The advantage of this method is its ability to estimate remnant cholesterol from a standard lipid profile without incurring additional costs or requiring specialized assay equipment [5 ▪ ].…”
Section: Definition Of Remnant Cholesterol and Measurementmentioning
confidence: 99%
“…TRLs are lipoproteins with a core rich in triglycerides, and include chylomicrons, VLDLs and IDLs. There are two primary sources of TRLs: intestine (chylomicrons) and liver (VLDLs) [5 ▪ ]. Triglycerides of exogenous origin are carried in apoB48-containing chylomicrons, while the triglycerides synthesized in the liver are mainly released in VLDL particles containing apoB100.…”
Section: Pathophysiology Of Elevated Remnant Cholesterol and Cad Due ...mentioning
confidence: 99%
“…These modifications encompass low HDL and low LPL activity in conditions of insulin deficiency, high TG and high VLDLs, normal or low VLDLs and increased HDLs in chronically insulin-treated patients with elevated LPL activity, and low HDLs in untreated T2D patients. In white adipose tissue, heightened LPL activity observed in obese and T2D individuals shares a common characteristic -hypertriglyceridemia, which is positively linked to adverse lipid accumulation in tissues (56,57). Insulin regulates the production and expression of LPL in adipocytes and in the skeletal muscle (58).…”
Section: Role Of Lpl Variants In Type 2 Diabetesmentioning
confidence: 99%
“…Various regulators influence LPL, including angiopoietin-like (ANGPTL) proteins (such as ANGPTL8, ANGPTL4, ANGPTL3) and certain apolipoproteins (including apolipoprotein A5, apolipoprotein C3, and apolipoprotein C2). These regulators collaboratively modulate LPL activity and the utilization of TG (57,58,82).…”
Section: Role Of Lpl Variants In Cardiovascular Diseasesmentioning
confidence: 99%
“…However, some observational studies have found that although maintaining LDL-c levels within a favorable range, the occurrence rate of initial or recurrent atherosclerotic cardiovascular disease (ASCVD) cannot be completely prevented due to residual risk [ 6 – 9 ]. These residual risks mainly originate from the triglyceride-rich lipoproteins (TRLs) and cholesterol components of metabolized TRLs (commonly referred to as remnant cholesterol) [ 10 , 11 ]. Non-high density lipoprotein cholesterol (non-HDL-c) is essentially comprised of remnant cholesterol and LDL-c, encompassing the total cholesterol content of all atherogenic lipoprotein particles [ 12 ].…”
Section: Introductionmentioning
confidence: 99%